Prescription audit of antihypertensive drugs used in stroke patients in a tertiary care teaching hospital - Shaji, Bipin; George, Jereena; Shrestha, Aishwarya; Stanly, Sharon Mary; Bose, Noah M. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Stroke is considered as one of the important reasons of death and disability worldwide. A rational use of medications is needed to prevent the recurrence and the disease related complications. Methods: The current study is a prospective observational study. All stroke cases, with patients above the age of 25 and treated with antihypertensive agents were included in the study. A total of 189 patients were found suitable for inclusion in the study. Using a suitably designed data collection form, all pertinent data such as patient demographics, prescribed medicines, drug interactions and adverse drug reactions were collected from the patient’s case file, nurses’ charts, and medication charts. Prescription pattern of antihypertensive drugs were obtained. The causality of the ADR was assessed using the Naranjo causality assessment scale and reported in the institution where the study was conducted. Results: Majority of patients included in the study were in the age group of 61-70 years. The incidence of stroke in this study was more in males than in the females. Ischemic stroke (72%) was more prevalent when compared to Hemorrhagic stroke. Among the antihypertensive agents, calcium channel blockers (32%) were the most commonly prescribed class of drugs. In our audit, drug related problems were observed in 27% of the cases which included cases with improper dose (3 cases), contraindications (4 cases), major drug interactions (20 cases), and adverse drug reactions (17 cases). Most of the prescriptions were legible. Drug related problems had a great impact on the overall stroketherapy. Conclusions: The drug related problems are a relevant aspect to be considered when treating patients with stroke and it can arise irrespective of adherence to guidelines.